(3JPcQI GdabgGAs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3UGdM Hf eMeO Hf MSf GdCadjMi s)
(3ChdgG (B:s
(3jHJOF HGdebUO GdKGdK ai CaYGd GdML s
(3BNQgG (B:s
(3jfJgi HCKfGA GdHjhY s
(3fSNI KGfjIs
(3jJdhg ai GdebUO GdQGHY GdaUd GdKGfi ai HjY GdfbOs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
Keywords: (3abg GdePGgH GdCNQis